Pengembangan Strategi PT ABC Niaga di Industri Distribusi Gas - Auguar Auguar; Muhammad Firdaus; Sahara Sahara (School of Business, Bogor Agricultural University (SB-IPB), 2017)
This study aims to analyze the development strategy of PT ABC Niaga in gas distribution industry. This study uses IFE and EFE Matrix, analysis SWOT matrix and QSPM. Prior to the analysis of the development of the strategy, first performed project feasibility analysis in the development plans of the city gas network from the aspects of company expenditure using capital budgeting. Then analyzed factors internal and external affecting business performance, SWOT analysis and formulated alternatives for the development of business strategies and their order of priority using QSPM. Analysis of internal and external factors each have a score of 2,541 and 3,261. QSPM matrix analysis shows that the strategy of